2018
DOI: 10.1002/ppsc.201800145
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional pH‐Responsive Sprayable Hydrogel Based on Chitosan and Lignin‐Based Nanoparticles

Abstract: Multifunctional sprayable hydrogels are widely developed for daily chemical and biomedical application. However, adding functional components and active ingredients is difficult to achieve uniform distribution and controlled release. Here, a new kind of lignin‐based nanoparticles is prepared, which can give hydrogels more functions (anti‐ultraviolet and antioxidant properties) and promote the response of hydrogels to pH stimulus. The nanocomposite hydrogels are engineered using carboxymethyl chitosan (CS) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Many recent studies used lignin‐based micro‐ and nanocapsules for sunscreen applications, relying on the natural UV absorbance of lignin and making use of synergistic effects between conventional, normally very hydrophobic sunscreen active substances and lignin . Qiu et al.…”
Section: Entrapment Encapsulation and Adsorption Of Active Substancmentioning
confidence: 99%
“…Many recent studies used lignin‐based micro‐ and nanocapsules for sunscreen applications, relying on the natural UV absorbance of lignin and making use of synergistic effects between conventional, normally very hydrophobic sunscreen active substances and lignin . Qiu et al.…”
Section: Entrapment Encapsulation and Adsorption Of Active Substancmentioning
confidence: 99%
“…Traditional dressings and sealants often require the use of antibiotics to prevent microbial infection [ 40 ]. Researchers have demonstrated that the incorporation of nanoparticles can endow hydrogels with antipathogenic properties [ 34 , 39 , 44 , 56 , 73 ], as well as add angiogenic, or adhesive properties [ 27 , 29 , 35 , 40 , 74 , 75 ], thus improving their use for wound healing [ 57 , 76 , 77 ].…”
Section: Wound Healingmentioning
confidence: 99%
“…Researchers are exploring other methods to create antimicrobial wound dressings using nanoparticles including pH sensitive drug delivery [ 47 , 76 ] and the use of phototherapy to generate reactive oxygen species (ROS) [ 36 , 57 ]. Zhu et al incorporated lignin-based NPs loaded with trans-resveratrol, a drug with antioxidant, immunomodulatory, anticancer, and anti-inflammatory activity, to carboxymethyl chitosan hydrogels.…”
Section: Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional dressings and sealants often require the use of antibiotics to prevent microbial infection [57]. Researchers have demonstrated the incorporation of nanoparticles can endow hydrogels with antipathogenic properties [39,54,[58][59][60], as well as add angiogenic, or adhesive properties [27,29,57,[61][62][63], thus improving their use for wound healing [64][65][66].…”
Section: Wound Healingmentioning
confidence: 99%